The Reality of Economic Diversification and Its Role in Promoting Algerian Foreign Trade During the Period 2010-2016 - Zahra, Moulefera Fatima; Fatna, Farsi (The journal of contemporary issues in business and government, 2023)
The study aimed to analyze and highlight the impact of economic diversification on foreign trade at the theoretical level and then attempt to apply this to the reality of economic diversification in Algeria during the period (2010-2016). Given that Algeria’s economy is heavily reliant on oil wealth, which is considered a finite resource threatened by depletion, the Algerian government deemed it necessary to transition from a rentier economy to a diversified one. This transition was achieved through a series of measures that aimed to bolster various economic sectors and encourage their penetration of international markets. The primary goal was to promote and diversify non-oil exports and eliminate export dependency on oil. However, it was concluded that economic diversification did not bring any significant value or change to Algerian foreign trade due to the continued reliance on oil exports by the government.